Nutritional status of children under five years of age and factors associated in rural areas of Sana'a Governorate, Yemen - Gawad M A. Alwabr (Wolters Kluwer Medknow Publications, 2021)
Background: The nutritional status of children determines their health, physical development, educational performance, and progress in life. This study aimed to assess the nutritional status and associated factors of children under 5 years of age in rural areas in Sana'a Governorate, Yemen. Materials and Methods: A descriptive cross-sectional study was conducted at five rural health centers of Sana'a Governorate, from March to May 2018. A convenience sampling method was used in the selection of 150 mothers and their children under five. A semi-structured questionnaire was used in data collection. According to WHO standards, the middle-upper arm circumference tool was used to measure the circumference of the upper part of the arm of the study children. Results: This study results showed that of all the children, 38.7% had Mild Malnutrition, 34% had Moderate Malnutrition, 6.7% had Severe Malnutrition, and 20.7% were normal. Majority of the participants' mothers (81.3%) were not knowledgeable about malnutrition causes. Place of delivery, mothers' education, fathers' education, age of mothers in the first pregnancy, numbers of all children per household, a child's weight at birth, and age of the child at weaning, were associated with the nutritional status of children under 5 years of age (P < 0.05). Conclusions: Despite the efforts of redressing child malnutrition issues in Yemen, the proportion of malnutrition among children under the age of five still high. Multiple intervention strategies based on risk factors can reduce early malnutrition of the children under the age of five.